Antioxidant-rich foods and response to altitude training: a randomized controlled trial in elite endurance athletes - Koivisto, A. E.; Paulsen, G.; Paur, I.; Garthe, I.; Tonnessen, E.; Raastad, T.; Ezzatkhah Bastani, N.; Hallén, J.; Blomhoff, R.; Kjølsrud Bøhn, S. (Scandinavian Journal of Medicine & Science in Sports, 2018)
High doses of isolated antioxidant supplements such as vitamin C and E, have demonstrated the potential to blunt cellular adaptations to training It is, however, unknown whether intake of high doses of antioxidants from foods has similar effects. Hence, the aim of the study was to investigate whether intake of antioxidant-rich foods affects adaptations to altitude training in elite athletes.